2013
DOI: 10.1074/jbc.m112.424416
|View full text |Cite
|
Sign up to set email alerts
|

ATP Hydrolysis Enhances RNA Recognition and Antiviral Signal Transduction by the Innate Immune Sensor, Laboratory of Genetics and Physiology 2 (LGP2)

Abstract: Background: Laboratory of genetics and physiology 2 (LGP2) is a cytoplasmic RNA receptor required for innate antiviral signaling. Results:LGP2 uses ATP hydrolysis to diversify RNA recognition and enhance antiviral signaling. Conclusion:LGP2 mediates antiviral responses by ATP-enhanced RNA recognition. Significance: This study reveals a novel property of LGP2 providing a mechanistic basis for its positive role in antiviral signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
130
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(150 citation statements)
references
References 27 publications
17
130
2
1
Order By: Relevance
“…This notion is supported by the characterization of an EMCV-derived MDA5 agonist RNA that was identified not on the basis of interaction with MDA5 but through its association with LGP2 (21). Replacing LGP2 with the enzymatically inactive K30A mutant by knock-in does not reconstitute defective positive signaling responses, indicating the importance of ATP hydrolysis in LGP2-positive regulation (19), but this same LGP2 mutant retains negative regulatory functions (14,22). Biochemical analysis and single-molecule RNA binding studies demonstrate that LGP2 uses ATP hydrolysis to enhance its ability to associate with diverse dsRNA species, enabling it to act in concert with MDA5 to maximize antiviral signal transduction (22,23).…”
supporting
confidence: 48%
See 3 more Smart Citations
“…This notion is supported by the characterization of an EMCV-derived MDA5 agonist RNA that was identified not on the basis of interaction with MDA5 but through its association with LGP2 (21). Replacing LGP2 with the enzymatically inactive K30A mutant by knock-in does not reconstitute defective positive signaling responses, indicating the importance of ATP hydrolysis in LGP2-positive regulation (19), but this same LGP2 mutant retains negative regulatory functions (14,22). Biochemical analysis and single-molecule RNA binding studies demonstrate that LGP2 uses ATP hydrolysis to enhance its ability to associate with diverse dsRNA species, enabling it to act in concert with MDA5 to maximize antiviral signal transduction (22,23).…”
supporting
confidence: 48%
“…LGP2 mutants that target helicase motif I (MI; K30A; defective for ATP hydrolysis but able to bind RNA [10]) or motif III (MIII; T167A S169A; defective for both ATP hydrolysis and RNA binding [10]) served as negative controls. These mutants fail to augment MDA5 signaling but retain negative regulation (22) (Fig. 1D).…”
Section: Generation Of a Biologically Activementioning
confidence: 99%
See 2 more Smart Citations
“…However, recently, Bruns et al demonstrated that robust basal ATPase activity allows LGP2 to diversify its RNA recognition capacity. 58 This result is interesting in light of the fact that both RIG-I and MDA5 completely lack basal ATPase activity. Moreover, the duck apo RIG-I structure suggests that ATP binding and hydrolysis can only occur in the presence of RNA.…”
Section: 5152mentioning
confidence: 78%